2024
DOI: 10.1126/sciadv.adk5260
|View full text |Cite
|
Sign up to set email alerts
|

Skin preparation–free, stretchable microneedle adhesive patches for reliable electrophysiological sensing and exoskeleton robot control

Heesoo Kim,
Juhyun Lee,
Ung Heo
et al.

Abstract: High-fidelity and comfortable recording of electrophysiological (EP) signals with on-the-fly setup is essential for health care and human-machine interfaces (HMIs). Microneedle electrodes allow direct access to the epidermis and eliminate time-consuming skin preparation. However, existing microneedle electrodes lack elasticity and reliability required for robust skin interfacing, thereby making long-term, high-quality EP sensing challenging during body movement. Here, we introduce a stretchable microneedle adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 69 publications
(99 reference statements)
0
0
0
Order By: Relevance
“…32−34 For example, Kim et al demonstrated a stretchable microneedle adhesive patch, characterized by excellent skin permeability and a robust electromechanical skin interface. 35 Zhang et al presented the sensors, adhering to the hairy scalp by generating negative pressure within their conical microstructures. 36 within seconds.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32−34 For example, Kim et al demonstrated a stretchable microneedle adhesive patch, characterized by excellent skin permeability and a robust electromechanical skin interface. 35 Zhang et al presented the sensors, adhering to the hairy scalp by generating negative pressure within their conical microstructures. 36 within seconds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Dry electrodes, devoid of the necessity for electrolyte gels, could circumvent the costs and intricacies that are caused by the periodic liquid replenishment in wet electrodes and also could alleviate the skin sensitivity induced by prolonged usage. Dry electrodes usually use nanomaterials such as carbon nanoparticles, graphene, and metal nanoparticles as conductive materials and add matrix materials like polymer, rubber, or silicone to enhance structural strength, forming conductive polymer composite electrodes. For example, Kim et al demonstrated a stretchable microneedle adhesive patch, characterized by excellent skin permeability and a robust electromechanical skin interface . Zhang et al presented the sensors, adhering to the hairy scalp by generating negative pressure within their conical microstructures .…”
Section: Introductionmentioning
confidence: 99%